Discharge characteristics of silver/lithium cobalt oxide cell for medical application - Kim, HS; Cho, WI; Cho, BW; Ju, JB (ELSEVIER SCIENCE BV, 2002)
The discharge capacity and storage characteristics of Ag/LiCoO(2) and Cu/LiCoO(2) cells are studied. The discharge capacity of the Ag/ LiCoO(2) cell is better than that of the Cu/LiCoO(2) cell. The Ag/LiCo02 Cell gives a maximum discharge capacity of 190 mAh g(-1). The structure of lithium cobalt oxide changes from trigonal to monoclinic, (a = 4.61 Angstrom, b = 2.81 Angstrom, c = 4.80 Angstrom, beta = 122.6degrees) system as the content of lithium is decreased. The Ag/LiCoO(2) cell shows good storage properties, there is little decrease in discharge capacity after 7 days at room temperature. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: LITHIUM